Assessing the alkyl chain effect of ammonium hydroxides ionic liquids on the kinetics of pure methane and carbon dioxide hydrates - Khan, M.S. (MDPI AG, 2020)
In this study, four ammonium hydroxide ionic liquids (AHILs) with varying alkyl chains were evaluated for their kinetic hydrate inhibition (KHI) impact on pure carbon dioxide (CO2) and methane (CH4) gas hydrate systems. The constant cooling technique was used to determine the induction time, the initial rate of hydrate formation, and the amount of gas uptake for CH4-AHILs and CO2-AHILs systems at 8.0 and 3.50 MPa, respectively, at 1 wt. aqueous AHILs solutions. In addition, the effect of hydrate formation sub-cooling temperature on the performance of the AHILs was conducted at experimental temperatures 274.0 and 277.0 K. The tested AHILs kinetically inhibited both CH4 and CO2 hydrates at the studied sub-cooling temperatures by delaying the hydrate induction time and reducing the initial rate of hydrate formation and gas uptake. The hydrate inhibition performance of AHILs increases with increasing alkyl chain length, due to the better surface adsorption on the hydrate crystal surface with alkyl chain length enhancement. TPrAOH efficiently inhibited the induction time of both CH4 and CO2 hydrate with an average inhibition percentage of 50 and 84, respectively. Tetramethylammonium Hydroxide (TMAOH) and Tetrabutylammonium Hydroxide (TBAOH) best reduced CH4 and CO2 total uptake on average, with TMAOH and Tetraethylammonium Hydroxide (TEAOH) suitably reducing the average initial rate of CH4 and CO2 hydrate formation, respectively. The findings in this study could provide a roadmap for the potential use of AHILs as KHI inhibitors, especially in offshore environs. Â© 2020 by the authors.